2001
DOI: 10.1097/00124509-200112000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Inefficacy of Burst-Suppression Anesthesia in Medication-Resistant Major Depression: A Controlled Trial

Abstract: Burst-suppression anesthesia (BSA) has been previously compared with electroconvulsive therapy (ECT) in drug-resistant depression, with promising results. We have carried out a double-blind randomized clinical trial comparing BSA with sham-BSA in 20 patients meeting DSM-IV criteria for major depression with inadequate response to antidepressant drugs and who chose BSA as an alternative to ECT. After withdrawing antidepressant drugs, patients were randomized to receive four sessions of either BSA (induction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…The explanation for why our results were more positive than other later studies may be due to closer adherence to the original protocols, particularly in patient age, dose/duration of each ISO session, and use of more ISO treatment sessions. As suggested by the QIDS-SR16 self-report data in Figure 2, much of the beneficial effect of ISO occurred in sessions 5–10, while Garcia-Toro et al terminated their treatments after only 4 sessions, and they used sevoflurane which might be less effective than ISO, especially if sustained EEG burst suppression is needed for a clinical benefit [14]. We also restricted our sample to persons aged 65 and younger, in part because of the increased likelihood of adverse blood pressure and cardiovascular concerns in elderly patients, like those studied by Greenberg et al [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The explanation for why our results were more positive than other later studies may be due to closer adherence to the original protocols, particularly in patient age, dose/duration of each ISO session, and use of more ISO treatment sessions. As suggested by the QIDS-SR16 self-report data in Figure 2, much of the beneficial effect of ISO occurred in sessions 5–10, while Garcia-Toro et al terminated their treatments after only 4 sessions, and they used sevoflurane which might be less effective than ISO, especially if sustained EEG burst suppression is needed for a clinical benefit [14]. We also restricted our sample to persons aged 65 and younger, in part because of the increased likelihood of adverse blood pressure and cardiovascular concerns in elderly patients, like those studied by Greenberg et al [13].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, however, Greenberg, et al [13] showed relatively little improvement with ISO treatments in a pilot study involving 6 elderly depressed patients (including 5 aged 74–82 years). In another pilot study, Garcia-Toro, et al [14] treated 10 patients with 4 treatments of low dose sevoflurane (approximately 2.5%). While a 24% reduction in depressive symptoms was noted on average, the clinical effect was not deemed sufficient after 4 treatments and patients were switched to ECT.…”
Section: Introductionmentioning
confidence: 99%
“…13 This technique is described in the European literature and has not been used with any degree of regularity in the United States. A thorough discussion of the safety and efficacy issues with burst suppression therapy is beyond the scope of this report, but suffice it to say that it represents a different procedure from using brief inhalational anesthesia for ECT.…”
Section: Discussionmentioning
confidence: 99%
“…Positive antidepressant effects of High ISO were reported by Carl et al [11] and Engelhardt et al [12]. In contrast, Greenberg et al [13] reported little improvement with High ISO treatments in 6 elderly depressed patients, and García-Toro et al [14] found only limited improvement after 4 prolonged treatments of low dose sevoflurane (24% reduction in depressive symptoms).…”
Section: Introductionmentioning
confidence: 94%
“…We suggested that the previous unsuccessful studies used too few treatments when, indeed, even the gold standard intervention, ECT, requires 8–12 treatments for maximal effectiveness. Also, we hypothesized that anesthetic treatment at doses that are too low to produce strong cortical BS (like the sevoflurane dose used by García-Toro et al [14]) would have minimal antidepressant effects. Thus, we compared responses of 8 patients with medication refractory depression treated with 10 sessions of High ISO with confirmed BS to 20 patients treated with bifrontal ECT.…”
Section: Introductionmentioning
confidence: 99%